Bacteriophage T4 Virion Baseplate Thymidylate Synthetase and Dihydrofolate Reductase - Kozloff, L. M. (1977)
Additional evidence is presented that both the phage T4D-induced thymidylate synthetase (gp td) and the T4D-induced dihydrofolate reductase (gp frd) are baseplate structural components. With regard to phage td it has been found that: (i) low levels of thymidylate synthetase activity were present in highly purified preparations of T4D ghost particles produced after infection with td(+), whereas particles produced after infection with td(−) had no measurable enzymatic activity; (ii) a mutation of the T4D td gene from td(ts) to td(+) simultaneously produced a heat-stable thymidylate synthetase enzyme and heat-stable phage particles (it should be noted that the phage baseplate structure determines heat lability); (iii) a recombinant of two T4D mutants constructed containing both td(ts) and frd(ts) genes produced particles whose physical properties indicate that these two molecules physically interact in the baseplate. With regard to phage frd it has been found that two spontaneous revertants each of two different T4D frd(ts) mutants to frd(+) not only produced altered dihydrofolate reductases but also formed phage particles with heat sensitivities different from their parents. Properties of T4D particles produced after infection with parental T4D mutants presumed to have a deletion of the td gene and/or the frd gene indicate that these particles still retain some characteristics associated with the presence of both the td and the frd molecules. Furthermore, the particles produced by the deletion mutants have been found to be physically different from the parent particles.